Effects of inclined magnetic field on mixed convection in a nanofluid filled double lid-driven cavity with volumetric heat generation or absorption using finite element method - Hussain, Shafqat; Öztop, Hakan Fehmi; Mehmood, Khalid; Abu-Hamdeh, Nidal (Elsevier, 2018)
A computational analysis has been performed on mixed convection in a double sided lid-driven cavity in the presence of volumetric heat generation or absorption. Effects of inclined magnetic field are also studied. The governing parameters are solved via Galerkin weighted residual finite element method in space and the Crank-Nicolson in time. Governing parameters are nanoparticle volume fraction (0.0 <= phi <= 0.04), Richardson number (0.01 <= Ri <= 10), internal heat generation or absorption parameter (-10 <= q <= 10), inclination angle of magnetic field (0 degrees <= gamma <= 90 degrees) and Hartmann number (0 <= Ha <= 100). It is observed that the highest heat transfer is obtained in case of the maximum value of heat absorption. As a further finding, heat transfer decreases with increasing of Hartmann number and increases with increasing of nanoparticle volume fraction.
Keywords: Numerical simulation; Nanofluid; Lid-driven cavity; Mixed convection; Finite element method; Inclined magnetic field